Effect of alkali addition on sulfur transformation during low temperature pyrolysis of sewage sludge - Cheng, S.; Qiao, Y.; Huang, J.; Cao, L.; Yang, H.; Liu, H.; Yu, Yun; Xu, M. (Combustion Institute, 2015)
© 2016 by The Combustion Institute. Published by Elsevier Inc.Odorous sulfur-containing gases released during sewage sludge processing cause significant environmental pollution. This study investigates the effect of alkali addition on sulfur transformation as well as the release of the sulfur-containing gases during sewage sludge pyrolysis at 150-450°C. The presence of alkali can promote the transformation of unstable organic aliphatic and aromatic sulfurs into more stable sulfoxides and sulphonic acid at low temperatures (i.e., 250°C). Alkalis also fix the inorganic sulfide and sulphate in char. Therefore, the release of the sulfur-containing gases can be greatly reduced with alkali addition. Stronger alkalis show more significant effect on the reduction of sulfur-containing gases, likely because of more OH radicals generated for the transformation of organic sulfurs.